Czech Republic : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
In this study, the following statistical data are presented in detail: composition of gross domestic product, industrial production, civil employment by factor, agricultural production, electricity production and consumption, developments in wholesale and consumer prices, operations of the central state budget, operations of local authorities, transfers to households, monetary survey, structure of domestic currency deposits, distribution of classified loans by maturity, selected interest rates, minimum reserve requirements, balance of payments, commodity composition of exports and imports, foreign direct investment by industry and country, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet